Non-tuberculous mycobacteria infection presenting as a hepatic allograft abscess - Anthony Robateau Colón; Eibhlin Higgins; Nicholas Boire; Nathan Cummins; Kymberly D. Watt (IDCases, 2023)
Nontuberculous mycobacteria (NTM) are mycobacterial species other than Mycobacterium tuberculous and Mycobacterium leprae [1]. They are environmental organisms which have been implicated in a wide array of clinical syndromes. Here we describe a case of a Mycobacterium fortuitum complex liver abscess in a liver transplant recipient.